2019
DOI: 10.30935/cet.554488
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Loneliness and Internet Addiction Level of College Students Based on Demographic Variables

Abstract: The aim of this study is to examine the loneliness and Internet addiction levels of college students in terms of demographic variables and to determine the variables that predict their Internet addiction level. Data were collected from college students studying at a public university in Turkey. The UCLA Loneliness Scale Version3 and Internet Addiction Test (IAT) were used as the data collection tools. College students were delivered an online survey and at the end 489 college students were voluntarily particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
0
11
0
4
Order By: Relevance
“…Numerous studies have reported strong connections of school burnout and Internet addiction with depression, anxiety, psychological distress, and stressful life events in adolescents and students [22,23,55,56,57]. Both constructs are also associated with social withdrawal, isolation, and loneliness [24,58,59]. Additionally, risky behaviors and health problems have been linked to school burnout and Internet addiction such as: alcohol and drug abuse, delinquency, and suicide ideation [34,35,60,61,62,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported strong connections of school burnout and Internet addiction with depression, anxiety, psychological distress, and stressful life events in adolescents and students [22,23,55,56,57]. Both constructs are also associated with social withdrawal, isolation, and loneliness [24,58,59]. Additionally, risky behaviors and health problems have been linked to school burnout and Internet addiction such as: alcohol and drug abuse, delinquency, and suicide ideation [34,35,60,61,62,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…An individual with Internet addiction often prefers the online world, or virtual reality, more than face-to-face social experiences (Malinauskas & Malinauskiene, 2019 ). Further, while the Internet provides a platform for dispelling negative emotions, such as loneliness, stress, sadness, or anxiety, those with excessive use end up with increased emotional distress as a result (Erol & Cirak, 2019 ). Internet addicts tend to feel “disconnected from reality” when they are online, which interferes significantly with daily functioning, due to chronic patterns of use and wasted time (Erol & Cirak, 2019 ).…”
Section: Internet Addictionmentioning
confidence: 99%
“…Further, while the Internet provides a platform for dispelling negative emotions, such as loneliness, stress, sadness, or anxiety, those with excessive use end up with increased emotional distress as a result (Erol & Cirak, 2019 ). Internet addicts tend to feel “disconnected from reality” when they are online, which interferes significantly with daily functioning, due to chronic patterns of use and wasted time (Erol & Cirak, 2019 ). For instance, excessive Internet users tend not to meet deadlines at work and neglect familial and peer relationships.…”
Section: Internet Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be acknowledged that, up to now, there are very few studies devoted to the fundamental and psychological foundations of addiction. At the same time, there is already a significant amount of research into neurobiological features of addiction (Zhang, Bai, Jiang, & Zhou, 2019;Baturay & Toker, 2019;Chen, 2019;Erol & Cirak, 2019;Dong & Potenza, 2014). In earlier studies, we assumed that our studies have shown that experience of computer game addiction of students is a process of creating a mental image virtual reality fundamentally transforms addict's psychic reality, which then begins to obey its own internal and independent laws, and these laws cannot be described in the framework of classical approaches to psychology.…”
Section: Introductionmentioning
confidence: 96%